Great River Monster: A Critical Approach from The Old Man and The Sea and other writings - Akter,, Md. Shaon (International Journal of Scientific Research and Management (IJSRM), 2017)
The Old Man and The Sea is the last work of Earnest Hemingway and here he proves that he is the greatestRiver Monster in the world. In the text Santiago caught a big fish that he had ever seen. Many writers createsome characters like Santiago in The Old Man and The Sea and Captain Ahab in Moby Dick and both try tobe River Monster but Santiago only becomes River Monster and gets victory because finally he defeats thefish like Monster and he proves himself as a great River Monster.